Risk factors for atrial fibrillation in dogs with dilated cardiomyopathy - Guglielmini, Carlo; Valente, Carlotta; Romito, Giovanni; Mazzoldi, Chiara; Baron Toaldo, Marco; Goncalves Sousa, Marlos; Wolf, Marcela; Beluque, Tamyris; Domenech, Oriol; Patata, Valentina; Porciello, Francesco; Ferrari, Paolo; et al. (Frontiers in Veterinary Science, 2023)
Introduction Atrial fibrillation secondary to dilated cardiomyopathy (DCM) frequently affects large-breed dogs. The aim of the present study was to identify risk factors for the development of atrial fibrillation in dogs of different breeds with an echocardiographic diagnosis of DCM. Methods In this multicenter retrospective study, we searched the electronic databases of five cardiology referral centers for dogs with an echocardiographic diagnosis of DCM. A comparison of clinical and echocardiographic variables was performed between dogs developing atrial fibrillation and those not developing atrial fibrillation and the ability to distinguish between these two groups of dogs was evaluated by receiver operating characteristic curve analysis. Univariate and multivariable logistic regression analysis estimated the odds ratio (OR) with 95% confidence interval (CI) of developing atrial fibrillation. Results We included 89 client-owned dogs with occult and overt echocardiographic DCM. Of these, 39 dogs (43.8%) had atrial fibrillation, 29 dogs (32.6%) maintained a sinus rhythm, and 21 dogs (23.6%) showed other cardiac arrhythmias. Left atrial diameter had high accuracy (area under the curve = 0.816, 95% CI = 0.719–0.890) to predict the development of atrial fibrillation at the cut-off of >4.66 cm. After multivariable stepwise logistic regression analysis, only increased left atrial diameter (OR = 3.58, 95% CI = 1.87–6.87; p < 0.001) and presence of right atrial enlargement (OR = 4.02, 95% CI = 1.35–11.97; p = 0.013) were significant predictors of atrial fibrillation development. Discussion Atrial fibrillation is a common complication of DCM in the dog and is significantly associated with increased absolute left atrial diameter and right atrial enlargement.